Sir George Dyson his life and music - Spicer, Paul (Boydell & Brewer, 2014)
George Dyson (1883-1964) was a highly influential composer, educator and administrator, whose work touched the lives of millions. Yet today, apart from his Canterbury Pilgrims and two sets of canticles for Choral Evensong, his music is little known. In this comprehensive and detailed study, based not only on Dyson's own writings but on unpublished papers, personal correspondence, and interviews with his family and friends, Paul Spicer brings this remarkable man and his lyrical, passionate and engaging music to life once more. Born into a working class family in Halifax, West Yorkshire, he rose from humble beginnings to become the voice of public school music in Britain and Director of the RCM. As a scholarship student, he met and studied with some of the leading musicians of the day, including Sir Charles Villiers Stanford and Sir Hubert Parry. He went on to work in some of the country's greatest schools, where he established his reputation as a composer, particularly of choral and orchestral works, of which Quo Vadis was his most ambitious. A member of the BBC Brains Trust panel, Dyson was also the 'voice of music' on the radio for a number of years and helped to educate the nation through his regular broadcasts. A fascinating, controversial man, George Dyson touched almost every sphere of musical life in Britain and helped to change the face of music performance and education in this country. This seminal book, examining every aspect of his long, colourful career, re-establishes him as the towering figure he undoubtedly was in his time. PAUL SPICER was a composition student of Herbert Howells, whose biography he wrote in 1998. He is well-known as a choral conductor especially of British Music of the twentieth century onwards, a writer, composer, teacher, and producer